An application of the Nerlove model to the Malaysian agricultural loans market - Habibullah, Muzafar Shah; Yusoff, Mohammed (Indian Institute of Economics, 1989)
Price expectations play an important role in producers' decision processes. For example. crop selection. crop planting and borrowing decisions involve uncertainties with regard to future income. Therefore. at the time when these decisions are made, producers have to formulate their expectations particularlv, about future prices or income in question. This is very important Because current decision affects future income and profits.